A new sufficient condition for blow-up of solutions to a class of parabolic equations. Issue 5 (3rd May 2016) - Zhu, Xiaoli; Li, Fuyi; Li, Yuhua
Abstract : In this paper, a new sufficient condition under which the solutions to a classical parabolic equation blow up is established. During this process, through constructing a new functional which falls between the energy and Nehari functionals, we also get a larger blow-up set.